2016
DOI: 10.1021/acs.nanolett.6b00609
|View full text |Cite
|
Sign up to set email alerts
|

Band Alignment and Minigaps in Monolayer MoS2-Graphene van der Waals Heterostructures

Abstract: Two-dimensional layered MoS2 shows great potential for nanoelectronic and optoelectronic devices due to its high photosensitivity, which is the result of its indirect to direct band gap transition when the bulk dimension is reduced to a single monolayer. Here, we present an exhaustive study of the band alignment and relativistic properties of a van der Waals heterostructure formed between single layers of MoS2 and graphene. A sharp, high-quality MoS2-graphene interface was obtained and characterized by micro-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
226
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(253 citation statements)
references
References 83 publications
24
226
1
2
Order By: Relevance
“…3c, which show how the low energy spectrum exhibits a finite gap for fully spin polarized bands. This band alignment agrees well with recent experiments in such bilayer system [29].…”
supporting
confidence: 93%
See 2 more Smart Citations
“…3c, which show how the low energy spectrum exhibits a finite gap for fully spin polarized bands. This band alignment agrees well with recent experiments in such bilayer system [29].…”
supporting
confidence: 93%
“…The SOC in the valence bands is much larger than in the conduction bands, with strength that varies with the transition metal [26]. Successful growth of graphene on MoS 2 and WS 2 has been demonstrated experimentally [22,[27][28][29][30]. First principles calculations on some of these systems have proved challenging [21][22][23], with reported results that differ qualitatively and quantitatively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The band profile and morphology have been revealed in previous STM/STS investigations, [22][23][24][25][26] and the opening of a band gap in graphene by overlaying a MoS 2 monolayer has been observed using angle-resolved photoemission spectroscopy. 27,28 However, the detailed connection between the atomic structure of the twisted heterojunction and the corresponding electronic structure is still lacking. Huang et al have visualized the moiré patterns clearly, and also shown using STS that the MoS 2 band gap is tunable by the local strain field.…”
Section: Introductionmentioning
confidence: 99%
“…G, MoS2, and h-BN are all chemically inert, avoiding bonding strongly when integrating with different dimensional crystals at the interface and leading to 2D-2D and 0D-2D (organic molecules-2D) van der Waals (vdW) heterostructures [25][26][27]. For example, MoS2-G vdW heterostructure shows that close to the Fermi level, no significant charge transfer doping is detected from MoS2 to G [28,29]. Besides, organic molecules are able to grow into well-ordered thin film with a high degree of crystallinity on 2D substrates and form vdW heterostructures.…”
Section: Introductionmentioning
confidence: 99%